P724 Vedolizumab use is not associated with increased malignancy incidence: GEMINI LTS study results and post-marketing data. (25th January 2019) - Card, T; Ungaro, R; Bhayat, F; Blake, A; Hantsbarger, G; Travis, S
Abstract: Background: Vedolizumab (VDZ) is a gut-selective antibody to α4β7 integrin approved for the treatment of moderate to severe Crohn's disease (CD) and ulcerative colitis (UC) in adults. Inflammatory bowel disease (IBD) and use of immunosuppressants are associated with increased risks of malignancy. We analysed the incidence of malignancy with VDZ using data from the GEMINI Long-Term Safety study (LTSS; NCT00790933) and post marketing data. Methods: Malignancies from the LTSS, and those reported in the VDZ Global Safety Database from 20 May 2014 (first approval of VDZ) to 19 May 2018, were identified using Medical Dictionary for Regulatory Activities terms. The number of patients with a malignancy in the LTSS (excluding malignancies within 1 year of VDZ initiation) was indirectly standardised against the number expected, using age- and sex-specific IBD rates from Optum's Clinformatics Data Mart database (CDMD), a de-identified claims database. Results: Of 2243 patients followed up for 7746 patient-years in the LTSS, 31 experienced a malignancy (17 CD, 14 UC); this was fewer than expected from the CDMD (31 vs. 62; ratio: 0.50 [95% CI: 0.34–0.71]; p < 0.0001; Table 1). The most common malignancies were renal and bladder (6) and lower GI (5). Prior anti-TNF agent use was reported in 61% of these patients and concomitant immunomodulator use in 39%. In the post-marketing setting, 299 malignancies were reported in 293 patients in the context of 208 050 patient-years of exposure (including malignancies within 1 year of VDZ initiation; Table 2): the most common were lower GI (59) and lymphoma (33). Prior and/or concomitant anti-TNF agent or other immunomodulator use was reported in 47% and 20% of these patients, respectively; 24% had no data on prior/concomitant treatment. Conclusions: The number of observed malignancies in the LTSS was lower than expected from the CDMD. As observed numbers are small, individual malignancy data should not be over-interpreted, and the limitation that standardisation does not correct for other potential confounders (e.g. smoking and body mass index) should be considered. Although limitations of post-marketing safety reports, including incomplete data and voluntary reporting of events, must be considered when interpreting post-marketing data, the number of malignancies with VDZ appeared low.